Crystal structure of 2,3-dimethoxy-N-(4-nitrophenyl)benzamide - Yaman, Mavişe (Acta Crystallogr E Crystallogr Commun, 2018)
In the title compound, C(15)H(14)N(2)O(5), the benzene rings are nearly coplanar, making a dihedral angle of 4.89 (8)°. An intramolecular N—H⋯O hydrogen bond occurs between the imino and methoxy groups. In the crystal, weak C—H⋯O hydrogen bonds link the molecules into supramolecular chains propagating along the a-axis direction. π–π stacking is observed between parallel benzene rings of neighbouring chains, the centroid-to-centroid distance being 3.6491 (10) Å. Three-dimensional Hirshfeld surface analyses and two-dimensional fingerprint plots have been used to analyse the intermolecular interactions present in the crystal.